Estado da arte sobre competências socioemocionais e articulação com políticas de avaliação (2012-2017) - Abatti, Thamiris Zanchim (2018)
The main objective of this work was to construct a State of the Art on Socio-emotional Competencies and Evaluation Politics, in order to identify possible articulations between the two themes. The State of the Art is a methodological resource that allows us to map and discuss academic production already performed in a given subject looking to different fields of knowledge and, presents an important exposure potential of this material previously evaluated and cataloged. The study sought to establish its theoretical basis on authors that promote the area of research both in the area that studies the model of Competencies and its implications, and in the area of Evaluation Politics, citing the implications of these theories in Brazilian territory as in large-scale assessments. To justify the State of the Art methodology, the research was based mainly on authors such as: Romanowski; Ens, 2006; Soares, 1999; Haddad, 2002; Brandão, 1986; Ferreira, 2002. The dissertation is divided into four thematic sections. In the first chapter we contextualize one of the main axes, the Competencies, the 1990‟s decade and the reforms that followed it and which were subsequently used as subterfuge for the appropriation of the Competency model. In chapter Two, we‟ve got researches documents about the relevance and the widespread of the Evaluation Politics, especially on the large-scale assessments and its effect in Brazil. In chapter three, we‟ve presented the methodology chosen for this study, the State of the Art with its respective works raised. Among the papers selected to compose the list of documents there are ten dissertations, one thesis and four scientific articles, all sharing the common axis on the keywords "Socio-emotional Competencies" or "Evaluation Policies". It is also important to mention that the research did not restrict only on the area of education, but it has covered other areas such as sociology, science, psychology, economics and design. In the fourth chapter and then in the final considerations, we have explained the joints found as a result of the study performed. It is highlighted that of the 8000 works found just two of them belongs to the area of education, and they discuss the relationship between "Socio-emotional Competencies" and "Evaluation Politics" creating the needing that we pay attention to the subject and its possible implications on discourses such as meritocracy, equity and the commercialize of education.